Comparisons of the Efficacy of Ligasure Hemorrhoidectomy in Grade 3 and 4 Hemorrhoid Diseases - Taşkin, Ali Kemal; Karademir, Enes (Journal of Coloproctology, 2024)
Objective In recent years, Ligasure hemorrhoidectomy has been preferred in the treatment of grade 3 and 4 hemorrhoids rather than traditional surgery. This study aimed to compare the efficacy of Ligasure hemorrhoidectomy in grade 3 and 4 hemorrhoid treatment.Methods A retrospective examination was made of the files of patients who underwent Ligasure hemorrhoidectomy because of grade 3 or 4 hemorrhoids. The demographic and clinical data of the patients were recorded. To evaluate pain severity after the procedure, a Visual Analog Scale (VAS) was used, and patient satisfaction at 6 months after the procedure was evaluated with a Likert-type scale. Early and late complications were determined in these follow-up examinations.Results The patients included in the study had a mean age of 45 ± 11 years and 82 (75.9%) were male. The mean follow-up period was 18 months (range, 6–44 months). The mean age of patients with grade 4 hemorrhoid was significantly higher than that of those with grade 3 hemorrhoid (p = 0.006). Postoperative early and late (relapse) complications were seen at a higher rate in grade 4 patients compared with grade 3, but the difference was not statistically significant. More successful treatment outcomes were observed in grade 3 patients than in those with grade 4 hemorrhoid, but not to a statistically significant level.Conclusion Ligasure hemorrhoidectomy is safer in terms of postoperative complications and treatment success is greater in patients with grade 3 hemorrhoids compared with those with grade 4 hemorrhoids.
Keywords: ligasure hemorrhoidectomy; grade 3–4 hemorrhoid; complication